Frequency of Toxoplasma and Toxocara Sp. Antibodies in Epileptic Patients, in South Western Iran - ALLAHDIN, Sudabeh; KHADEMVATAN, Shahram; MOMEN, Aliakbar; RAFIEI, Abdollah (Iranian Journal of Child Neurology, 2015)
How to Cite This Article: Allahdin S, Khademvatan S, Rafiei A, Momen AA, Rafiei R. Frequency of Toxoplasma and Toxocara Sp. Antibodies in Epileptic Patients, in South Western Iran. Iran J Child Neurol. Autumn 2015;9(4):32-40. Abstract Objective Epilepsy is a disorder of the brain characterized by an enduring predisposition to generate seizures. Infectious agents are mentioned in its etiology. With identifying and appropriate treatment of these infectious agents, preventing their secondary outcomes, including seizure is possible. This study was conducted to determine frequency of anti-Toxoplasma antibodies (IgG, IgM) and anti- Toxocara antibody (IgG) in epileptic patients. Materials & Methods Study sample consisted of 141 epileptic patients and 144 healthy people. After obtaining informed consents and completing demographic questionnaire, serum samples were taken from participants. The diagnostic test of Toxoplasma IgG & IgM and Toxocara antibodies was performed under the same conditions using ELISA method in a qualified private laboratory. Samples from patients and control groups with positive ELISA test in terms of anti-Toxocara antibody were also used for confirmatory Western blot test. Result According to ELISA results, 28 (19.85%) epileptic patients and 2(1.38%) of healthy people had anti-Toxocara antibodies (P<001), while 39 (30.46%) of the control group people and 14.18% of patients had anti-Toxoplsma antibodies (P=0.001). Conclusion Frequency of anti-Toxoplasma gondii is lower in epileptic than healthy individuals and this result is contrary to investigations that have reported higher levels of this antibody in such patient groups. ELISA results for Toxocara showed that the frequency of anti-Toxocara antibody in epileptic patients might empower the probability that this parasite may cause central nervous system damage. Western blotting has high specificity and is a proper confirmative method for diagnosis of toxocariasis.